Avaliação de um procedimento para aquisição de leitura em crianças com diagnóstico de autismo - Santos, Larissa Chaves de Sousa (2012)
Individuals with autism spectrum disorder diagnosis, overall, present deficit in communication, social interaction and repeatable behavior. The difficulties of learning in this population, often, are results of establishment of a restrict stimulus control. This study had as objective to evaluate a procedure that allow an emergency reading with comprehension and allowing the restrict stimulus control truth the teaching process. The research was made within two autism patients, both seven years old. It was used four words with two syllables divided in two groups of words, using the consonant-vowelconsonant- vowel. The teaching process was made using the matching to sample , It were trained the relations in between hearing stimulus, pictures, printed words and anagrams constructions. During the training it was inducted extra corrections procedures that avoided the incorrect stimulus control. These extra procedures were made depending on the difficulties presented by the patients. The equivalence tests for the new verbal forms and the naming stated that the training for patient 1 was enough for the emergency reading within comprehension. Patient 2 used only part of the procedure, because the data colleting period was insufficient to amplify his initial repertory. It were concluded that the used extra procedures during the teaching were important variables to the procedure effeteness